Isolation and characterization of Saccharomyces cerevisiae for the production of ethanol from organic sources - Rahman, Shafkat Shamim (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2013.